2014
DOI: 10.1590/1678-41625929
|View full text |Cite
|
Sign up to set email alerts
|

Valores nutricionais do milho de diferentes qualidades para frangas de reposição na fase de recria

Abstract: MDB. To determine the corrected metabolizable energy (AME N ) a method for total collection of excreta with pullets Hy Line was used for 15 weeks. AME N (kcal/kg in MN) were: 3467, 3340, 3217 and 3385kcal/kg and density (kg/m 3 ): 818.61, 698.13, 681.80 and 736.39 for MDA, MDI, MDB and MDT, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
4
2
Order By: Relevance
“…The CP level can be influenced by regional factors, especially by the type of nitrogen fertilization applied during the cultivation of the kernels. There was no linearity in the relationship between CP and the different fractions, contrary to the linear and inversely proportional response reported in the literature (10,13) . This finding was expected due to the decreasing concentration of starch in the kernels with lower specific weight, which resulted in a higher concentration of other nutrients 14 .…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…The CP level can be influenced by regional factors, especially by the type of nitrogen fertilization applied during the cultivation of the kernels. There was no linearity in the relationship between CP and the different fractions, contrary to the linear and inversely proportional response reported in the literature (10,13) . This finding was expected due to the decreasing concentration of starch in the kernels with lower specific weight, which resulted in a higher concentration of other nutrients 14 .…”
Section: Resultscontrasting
confidence: 91%
“…However, AME DM showed a quadratic behavior, with the lowest estimated level found at the specific gravity of 769 kg/m 3 (Table 4, Figure 1). Studies found in the literature describe an increase in AME values directly proportional to the specific gravity of kernels (10,13,14) . The highest GE value, which was found in the kernels with the highest specific gravity (Table 5), did not convert into higher AME values when the specific gravity of the maize fractions increased.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The determination of feed energy values used to formulate diets is difficult for the industry because it takes time, infrastructure, and financial resources (Pozza et al, 2008). An indirect way to evaluate the nutritional quality of this raw material is the use of prediction equations including determination of metabolizable energy using chemical and physical parameters of the feed (Eyng et al, 2009;Corte Real et al, 2014). This equation has been an important tool to increase accuracy in the feed formulation process, so energy values can be corrected according to variations in the composition of the feed (Albino and Silva, 1996;Barbarino Junior, 2001), as most chemical analysis of corn and other ingredients used in equations to infer energy values are often not consistent with those measured in metabolic assays (Corte Real et al, 2014).…”
Section: Introductionmentioning
confidence: 99%